Yangtze river protection law of the Peoples Republic of China overview of key provisions and policy recommendations. - Yee, Au Shion; Guo, Dongmei; Michael G. (ADB briefs., 2021)
The YRPL represents a legislative landmark for strengthening policy and regulatory frameworks to achieve environmental protection in the PRCs largest and most significant river basin. The policy recommendations presented here were prepared under ADBs technical assistance project to provide technical guidance on the formulation and design of the YRPL covering the following areas: (i) institutional coordination, (ii) policy mechanisms, (iii) environmental and water quality standards, (iv) monitoring methods and systems, and (v) environmental flow assessment.